Persistent neurocognitive abnormalities as clinical sequelae of mild to moderate COVID-19 - Bednarska, Agnieszka; Radkowski, Marek; Laskus, Tomasz; Bursa, Dominik; Bluszcz, Natalia; Makowiecki, Michał; Sosińska-Bryła, Iwona; Paciorek, Marcin; Porowski, Dawid; Hackiewicz, Małgorzata; Kowalska, Justyna; Furman-Dłubała, Anna; et al. (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to examine the incidence of symptoms that indicate neurological or pulmonary complications after recovery from mild to moderate COVID-19.MethodsThe study included 138 adult outpatients who underwent testing that included chest X-ray (CXR), complete blood count (CBC), C-reactive protein (CRP), interleukin 6 (IL-6), and D-dimer assessments during the acute phase of the illness. In addition, 30 days after being classified as convalescent, serological tests for IgM and IgG antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were performed, and the patients were asked to complete a survey assessing their overall wellbeing.ResultsThe most common sequelae included decreased physical efficiency (35%), weakness (24%), difficulty concentrating (16%), and memory problems (15%), which were correlated with abnormal chest X-ray findings. Seroconversion to anti-SARS-CoV-2 IgG was detected in 49 (87.5%) out of 56 patients tested and was more common among those with a more severe course of the infection.ConclusionIndividuals with mild to moderate COVID-19 are likely to experience persistent neurocognitive symptoms. Patients with initial abnormal chest X-ray findings and elevated inflammatory parameters are more likely to seroconvert to anti-SARS-CoV-2.